Synergistic Electrochemical Performance of CoFe2O4/Polypyrrole Composite Electrodes for Supercapacitor Applications - Najem, Israa A.; Najm, Asmaa Adnan; Gencten, Metin; Birol, Burak (ELECTROCHEMICAL SOC INC, 2026)
Hybrid electrode materials combining transition metal oxides and conductive polymers have attracted significant attention for supercapacitor applications. In this study, cobalt ferrite nanoparticles were synthesized via sol-gel method, and polypyrrole conductive polymer was prepared by chemical oxidative polymerization method. Composite electrodes were fabricated with different CoFe2O4/PPy rations and evaluated in 6 M KOH electrolyte. electrochemical analyses revealed stable operation within potential window 0 f 0-1.4 V and a hybrid charge storage mechanism combining electric double-layer capacitance and pseudocapacitance. Among the investigated samples, the CF6P2 electrode exhibited the best performance, delivering a specific capacitance of 296 mF cm-2 (161 F g-1) at 1 mV s-1, along with an energy density of 50.35 Wh kg-1. In addition, it demonstrated good cycling stability with 95% capacitance retention after 5000 cycles. The enhanced performance is attributed to the synergistic interaction between CoFe2O4 and PPy, which improves electrical conductivity and redox activity.
Keywords: cobalt ferrite (CoFe2O4); polypyrrole (PPy); hybrid electrode materials; supercapacitors; pseudocapacitive behavior; ANODE MATERIAL; CONDUCTIVE POLYPYRROLE; GRAPHENE OXIDE; NANOPARTICLES; FABRICATION; FIBER; Materials Science; Physics